Development of continuous process for the preparation of tetraethyl orthosilicate through the reaction of metallurgical silicon with ethanol in the presence of base salt catalyst - Kim, Dae Jin; Hong, Chang Seop; Yoo, Bok Ryul (한국공업화학회, 2022)
In this study, tetraethyl orthosilicate (TEOS) was synthesized by the continuous reaction of metallurgical silicon (MSi) with ethanol. The results obtained herein suggest that among all the alkali metal base catalysts, diethylene glycol monoethyl ether sodium (DEGEE-Na) is the best catalyst; this is because it does not require any extra diethylene glycol monoethyl ether (DEGEE-H) as excess DEGEE-H results in its decomposition products. It is present in a solid phase at room temperature; however, it changes into a liquid phase under the reaction conditions. In contrast, DEGEE-Li was not suitable for this reaction, whereas DEGEE-K required extra DEGEE-H as a solvent because of the solidification of the reaction mixture in the reaction with MSi. When the continuous reaction was carried out by feeding ethanol into a mixture of MSi and DEGEE？Na salt catalyst (1:1 wt.% ratio) at 175 °C, TEOS was obtained with a yield of 70.6%. In addition to TEOS, small amounts of byproducts, such as (2-ethoxyethoxy)triethoxysilane and hexaethoxydisiloxane were obtained and unreacted ethanol was recovered and recycled. For the preparation of TEOS, activation of MSi is an important step in the reaction with ethanol. We believe that this continuous process for preparing TEOS is more economically competitive and eco-friendly method.